IMPACT OF FSA RESTRUCTURING ON OPERATIONAL RISK REGULATION IN UK - Tunuguntla, Venkata Santosh (2013)
This research analyzes the impact of FSA restructuring into FCA and PRA, on operational risk regulation within the UK and its implications on financial institutions. A semi-structured telephonic interview method was used for the purpose of collecting the data from a sample of 5 operational risk SME's from different financial institutions. Qualitative Inductive approach was used to analyze the data collected from the interviewees and key themes were drawn accordingly. Findings and Analysis unveil that conduct risk regulation, additional operational risk disclosure requirements and new corporate governance requirements are the significant changes introduced newly by FCA and PRA which has a direct impact on operational risk management of the financial institutions. This research investigates the possibility of overlap/underlap between FCA and PRA that can result in operational challenges to the financial institutions. Also, the findings and analysis unveils the different challenges the financial institutions will have to face due to the changes introduced by FCA and PRA to operational risk regulation.